Hydrothermal properties of the COS/D2 water model: a polarizable charge-on-spring water model, at elevated temperatures and pressures1. Issue 93 (11th October 2015) - Steele-MacInnis, Matthew; Reimer, Joachim; Bachmann, Stephan
<x xml:space="preserve">Abstract</x> Molecular simulations have been conducted to assess the pVT properties and static permittivity of the charge-on-spring polarizable water model COS/D2 at hydrothermal conditions from 300 to 450 °C and bulk densities of 0.001 to 1.0 g cm−3.